Perancangan Dashboard Berbasis Business Intelligence untuk Optimalisasi Manajemen Persediaan di CV Bali Treasures - Callysta Athalia Anak Agung Istri; I Made Dendi Maysanjaya; Gede Surya Mahendra (UNIB Press, 2025)
The global landscape is undergoing a digital transformation marked by the Fourth Industrial Revolution and the move toward society 5.0. Companies are expected to manage data efficiently. CV Bali Treasures, a percussion instrument manufacturer, still records wood-based production data manually using Microsoft Excel, complicating trend analysis and decision-making. This study implements a Business Intelligence (BI) dashboard using Microsoft Power BI to improve raw material inventory management. The methodology follows the BI Roadmap using data from the Processed Wood Inventory Mutation Report (LMHHKO) from March 2019 to September 2024. System evaluation was conducted through User Acceptance Testing (UAT) with the Black Box Testing method involving five users. The results show the dashboard effectively visualizes inventory data, supports data historical analysis, and speeds up decision-making. Users confirmed the dashboard met their needs and was easy to use. This BI implementation is expected to support digital transformation and enhance the company's efficiency and competitiveness.